Studies on in vivo seed germination & in vitro embryo rescue technique in wild banana (Musa acuminata) - Chairil Rizal Ramli (2012)
Two distinct technique, in vivo and in vitro technique (embryo rescue) were applied to determine which one is the best way to germine wild banana seeds for research purpose. This research also includes the comparison of germination rate of highland banana and lowland banana, the morphology and characteristic of each seed and embryo and also dormancy state of Musa acuminata spp. malaccensis. Study on in vitro technique had been carried out on three population collected from three different locations. Two populations were collected from the lowland area alleviation of 98 m (Meranto and Jeli population) and the other population was collected from highland area alleviation of 387 m (Gunung Chamah). The media culture used is MS supplemented with 2 mg of BAP hormones. The in vivo technique, studies were carried only in lowland wild banana ( Meranto population) by sowing seeds in two type of medium, mix soil and sand, to study the relationships between medium and the rate of seed germination. High scale mass of wild banana plantlets can be produce by using in vitro technique compare to in vivo technique. However, the micro propagation will succeeded if the level of contamination occurred can be controlled. Highland banana and lowland banana has greater differences between their characteristics. Highland banana have small size of seeds, and flattened embryo-shaped while lowland banana have quite bigger size of seeds, and mushroom like shape of embryo. Those characteristics were influenced the sterilization technique of culture initiation. Mix of sand and compost has a good potential to support the growth of wild banana seeds compare to sand medium.